STRATEGI BAREFOOT COLLEGE DALAM MEMBERDAYAKAN PEREMPUAN MELALUI PROGRAM SOLAR MAMAS - Savilah, Dwi Arni Intan; Retnaningsih, Umi Oktyari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2026)
The involvement of women in the renewable energy sector is not only an achievement of gender equality, but also a crucial strategy for achieving sustainable energy security. Barefoot College has developed a strategy for empowering women in the renewable energy sector by positioning women as technical actors and decision makers through the Solar Mamas program. The main focus of this study is to understand how NGOs have succeeded in breaking down societal stigma against women who face limitations due to patriarchal cultural traditions. This research uses qualitative methods with a descriptive analysis approach and is analyzed using the Non-Governmental Organization (NGO) theory according to David Lewis and Nazeen Kanji, 2001. The research data was obtained through secondary data in the form of official reports from Barefoot College, international organizations, and other reading sources related to the issues discussed in this theme. The findings revealed of study show that Barefoot College has been successful in empowering women through the Solar Mamas program. The strategy used by Barefoot College is based on a traditional approach to the community, as well as efforts to empower women and support the Solar Mamas community after the program is completed. With this, Barefoot College has demonstrated the success of the program in achieving the SDGs. Keywords: Barefoot College, Renewable Energy, Solar Mamas Program, Women's Empowerment.